HEMODIAFILTRATION WITH SELF-CLEANING SYSTEM - DRAGHICI Dumitru Adrian; REPANOVICI Angela; FOTEA Silvia; NECULA Radu Dan; SCUTARIU Mihaela Monica; CRETU Oana-Cristina; PANTEA Ileana (ACTA TECHNICA NAPOCENSIS SERIES-APPLIED MATHEMATICS MECHANICS AND ENGINEERING, 2024)
Hemodiafiltration (HDF) is considered the primary method for replacing kidney and liver function through blood filtration. Strong convective flows have been linked to improved clinical outcomes, but achieving high blood flows for effective convective therapies can be challenging due to technical obstacles and the risk of defense cell blockages in the filtration system. Despite optimized procedures, issues such as increased transmembrane pressure, blood viscosity, and filter clogging may still arise. To address these challenges, two potential solutions are proposed: automatic predilution and automatic backflush. Predilution involves diverting a portion of filtered dialysate in the opposite direction from filtration at regular intervals to achieve hemodilution and improve filter performance. Backflush, triggered by TMP control, involves infusing ultrapure dialysate into the filtration system to improve hemodilution and clean membrane pores. These innovations aim to overcome technical barriers and ensure effective convective dose delivery in HDF treatment.
Keywords: hemodiafiltration; convection; ultrafiltration; predilution; back filtration